Data Feminism as a guide for agricultural research - Nichols, Virginia; Carter, Angie; Gailans, Stefan; Basche, Andrea; Weisberger, David (Npj sustainable agriculture, 2025)
Agricultural research reflects complex institutional and interpersonal relationships that have historically been, and continue to be, subject to power imbalances. Recently, interdisciplinary scholars developed the Data Feminism framework to aid scientists in understanding and addressing power in research. In this Perspective, we demonstrate the framework’s utility in agricultural research and present evidence that explicit attention to power, reciprocity and values fosters both research creativity and positive societal outcomes.